Pressure loss prediction and control model for water treatment units - Abbas, Estabraq Khudhair (2014)
Water treatment compact units are widely applied in Iraq for production of drinking water. Treated water quality meets world Health Organization (WHO) standards. Present work focuses upon compact water treatment units design, power and pressure drops control modeling and simulations. Computer program software (compact pro) was developed to calculate the pressure losses in piping network and process equipment's. Results obtained for pressure drop unit length for different pipe diameters and roughness, show that for pipe diameter above (200 mm) for (200 m 3 /hr),water pressure drop almost the same, while for pipe diameter less than (200 mm), water pressure drop is minimum for PVC and Stainless steel and maximum for galvanized steel. As the piping roughness increase, pressure drop will increase in general for any water internal flow rate. As internal flow rate increased, water pressure drop increase .This result is very important for process designer. Comparisons between results of Compact Pro Software and Pipe flow expert Software for different Input data, shows a good agreement which not exceed 8.6% as maximum. There are only slight change in pressure and pressure drop to the proposed model for compact water treatment unit, sensible change in pressure and pressure drop in the sand filtrations stage. Power calculations for the two water treatment stages, including shaft power for pumps motors for different piping materials. Results show that power can be saved up to more than 85 %.